Knowledge, attitude and consumer preferences of students in relation to genetically modified organisms - Torres, Romulo G. III
Over the years, the prevalence of Genetically Modified Organisms (GMO) in food commodities has steadily increased. Almost every processed food made from corn, potato and soy is genetically modified. A continued interest in GMO exists because many of the issues pertaining to the technology behind it are yet to be resolved. There is no real way to do a risk - benefit analysis when most of the information about GMO is unclear. Moreover, there are still no global standards that are set about GMO. Each and everyone you ask about GMO have their own version of what is true and what is not. The objective of the study was to determine if a student's scholastic environment has an effect on his/her intrinsic knowledge, attitudes, and consumption preferences with regards to GMO. This study is helpful in measuring the implicit knowledge that students possess about GMO and suggests possible information dissemination strategies that schools may employ to increase knowledge and awareness about GMO. The data gathered regarding student attitude and its relationship with environmental factors were helpful in designing intervention methods in influencing attitudes towards GMO, consumer behavior and preference towards eating GMO. The research was a cross-sectional utilizing a 2 x 3 factorial design. The respondents for the study were determined using purposive random sampling, consisting of students from the College of Home Economics specifically the B.S Food Technology (BSFT), B.S Community Nutrition (BSCN), B.S Clothing Technology (BSCT), and B.S Interior Design (BSID) students. A two-tailed test was used to find out if there was a significant difference between the knowledge, attitude, and consumption preference towards GMO of students with different scholastic environments. The results suggested that at present, there is no difference in the knowledge about GMO of students who participated in the study. They, however, differ in the attitude they express towards issues regarding GMO, and preference of foods that contain GMO. Students who have GMO-related subjects, BSFT, and BSCN students showed a more positive attitude and preference towards GMO. It is recommended that students be more conscious on their basis for consumer decisions regarding GMO. It is also recommended that teachers be more objective in teaching GMO-related subjects to avoid subjective influence in student attitude toward GMO. In addition, the present government is urged to establish credibility with regards to information dissemination about GMO in order to promote the success of the Department of Agriculture's biotech programs. Lastly, it is recommended that the biotech industry continue reflecting a positive attitude towards GMO to be able to increase potential profits from their products. In future researches, it is recommended that standardized tests about GMO measuring factual knowledge and practical applications must be developed. An increased number of items per area or category such as issues on health, economics, environment and ethics, is helpful in assessing student attitudes towards GMO. An increased number of questions that describe scholastic environment must also be used to better characterize the learning environment where student consumers are immersed in.